Nitrogen in the Environment: Sources, Problems, and Management - R.F. Follett; J.L. Hatfield (The Scientific World Journal)
Nitrogen (N) is applied worldwide to produce food. It is in the atmosphere, soil, and water and is essential to all life. N for agriculture includes fertilizer, biologically fixed, manure, recycled crop residue, and soil-mineralized N. Presently, fertilizer N is a major source of N, and animal manure N is inefficiently used. Potential environmental impacts of N excreted by humans are increasing rapidly with increasing world populations. Where needed, N must be efficiently used because N can be transported immense distances and transformed into soluble and/or gaseous forms that pollute water resources and cause greenhouse effects. Unfortunately, increased amounts of gaseous N enter the environment as N2O to cause greenhouse warming and as NH3 to shift ecological balances of natural ecosystems. Large amounts of N are displaced with eroding sediments in surface waters. Soluble N in runoff or leachate water enters streams, rivers, and groundwater. High-nitrate drinking water can cause methemoglobinemia, while nitrosamines are associated with various human cancers. We describe the benefits, but also how N in the wrong form or place results in harmful effects on humans and animals, as well as to ecological and environmental systems.